Alveolar echinococcosis in a dog in Missouri, USA. (July 2022) - Kuroki, Keiichi; Morishima, Yasuyuki; Dorr, Lindsay; Cook, Cristi R.
A 10-y-old, castrated male Boxer dog that was born and had lived in Missouri without any travel history to other states, except for a few trips to Kansas, was presented with a distended abdomen and declined health. Ultrasonographic examination revealed a large hepatic mass, and the dog was euthanized. A postmortem examination revealed that the left liver lobes were largely replaced by a white-to-tan multilobular mass with a cobblestone surface. The lesion also involved the diaphragm. Histologically, hepatic architecture was effaced by large areas of necrosis with numerous, ≤0.2-cm, cystic structures that stained positively with periodic acid–Schiff stain and contained calcareous corpuscles. Gross and microscopic hepatic lesions were compatible with alveolar echinococcosis (AE) caused by Echinococcus multilocularis . PCR examination confirmed E. multilocularis, and results from genotyping were consistent with the E4 haplotype. To our knowledge, this is only the second canine AE case and the third pet dog that has been confirmed to be infected by E. multilocularis in the contiguous United States. E. multilocularis is a serious health risk for both pet dogs and humans.